Cholesterol-Lowering Effect of Polysaccharides from Cyclocarya paliurus In Vitro and in Hypercholesterolemia Mice - Yang Zhang; Lei Zeng; Kehui Ouyang; Wenjun Wang (Foods, 2024)
In this study, a new component of Cyclocarya paliurus polysaccharides (CPP20) was precipitated by the gradient ethanol method, and the protective effect of CPP20 on hypercholesterolemia mice was investigated. In vitro, CPP20 had the ability to bind bile salts and inhibit cholesterol micelle solubility, and it could effectively clear free radicals (DPPH•, •OH, and ABTS+). In vivo, CPP20 effectively alleviated hypercholesterolemia and liver damage in mice. After CPP20 intervention, the activity of antioxidant enzymes (SOD, CAT, and GSH-Px) and the level of HDL-C in liver and serum were increased, and the activity of aminotransferase (ALT and AST) and the level of MDA, TC, TG, LDL-C, and TBA were decreased. Molecular experiments showed that CPP20 reduced cholesterol by regulating the mRNA expression of antioxidation-related genes (SOD, GSH-Px, and CAT) and genes related to the cholesterol metabolism (CYP7A1, CYP27A1, SREBP-2, HMGCR, and FXR) in liver. In addition, CPP20 alleviated intestinal microbiota disturbances in mice with hypercholesterolemia and increased levels of SCFAs. Therefore, CPP20 alleviates hypercholesterolemia by alleviating oxidative damage, maintaining cholesterol homeostasis, and regulating gut microbiota.